Tinjauan Aspek Keuangan dalam Kelayakan Usaha Pendirian Bank Perkreditan Rakyat - Wulanditya, Putri (UNUSA Press, 2016)
In the framework of establishment of the BPR, one of the main aspects of therequirements is the receipt of the feasibility study. From some aspects evaluated in thebusiness feasibility of BPR, one of which is the financial aspect. Based on this, the insideof this article would like to express a problem about How to perform feasibility analysisBPR establishment in terms of financial aspect? According to the problems disclosed, thepurpose of this research is to know how to calculate, assess, and analyze the feasibility ofthe viewpoint of the financial aspects. This study uses data projected financial statementsfor the first 5 years of operations of PT BPR Elbaghraf. The method used included explorativedescriptive analysis using quantitative and qualitative approaches. The results of thefeasibility analysis of investment is reflected in the value of IRR of 17.89%, PP by 4.96and Benefit and Cost Ratio (B/C) ratio of 1.68. Indicates that the planned establishmentof PT BPR Elbaghraf feasible to be realized from the financial feasibility assessment.While based on the financial performance of the financial projections for 5 years initialoutline operational bank is also considered feasible. Based on the analysis of the feasibilitystudy, the project is expected investment in PT BPR Elbaghraf in Sumenep can beimmediately executed. For Commissioners and Board of Directors, will be able to makeprojections on the financial statements as a reference in pengoperasional BPR during thefirst 5 years. So that with the presence of the new BPR in Sumenep can contribute directlyto encourage the economic growth rate in the area of Sumenep.